If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4r+9=-7(-6+r)
We move all terms to the left:
4r+9-(-7(-6+r))=0
We add all the numbers together, and all the variables
4r-(-7(r-6))+9=0
We calculate terms in parentheses: -(-7(r-6)), so:We get rid of parentheses
-7(r-6)
We multiply parentheses
-7r+42
Back to the equation:
-(-7r+42)
4r+7r-42+9=0
We add all the numbers together, and all the variables
11r-33=0
We move all terms containing r to the left, all other terms to the right
11r=33
r=33/11
r=3
| 10y=4y+6 | | 14x-29=83 | | 32=-412x | | 0.2x+4=x+3 | | x/2-14=11 | | 8x-27=21 | | 9x+3-5x=4x+3 | | x^2+8=540 | | -7(z+6)=-56 | | 2^n=8^20 | | 2=m-13 | | 9-3/4(3x-16)=48 | | -8x-8=-4(2-3x) | | (40y+30)=5 | | 25x+30=125 | | 8=b4+ 4 | | 7e+1=3+5 | | –174=3x | | f-13=6 | | 12=-39+3x | | p=-6(8p-8)+p | | 12=6×a | | 10x-10+12x-4+x=180 | | 118+60+x=180 | | 3.1x=380 | | (3x-1)2=(10x-26) | | 6.8-1.3x=0.6x-2.7 | | 0.2g-1.8=-2.6 | | 4w+-3.7=-15.7 | | ∠1=3y-6 | | 0.7(h+9)=0.63 | | -4x(x-2)=(3x-8) |